Characteristics of clinical manifestations and molecular genetics of inherited hyperhomocysteinemia in children and adolescents: a single center experience from China - Qu, Rui; Han, Aimin; Zhao, Yang; Qu, Xiangju; Zhu, Yali (Frontiers in Neurology, 2025)
Introduction:Accurate identification of the genetic cause of inherited hyperhomocysteinemia (HHcy) is essential for targeted therapies and individualized treatment. However, reported cases in China remain limited. In this study, we investigated the clinical and molecular genetic characteristics of HHcy in Chinese children/adolescents.MethodsBetween 2021 and 2024, eight children/adolescents with inherited HHcy were identified at a tertiary hospital. The patients' clinical presentations, biochemical findings, and genetic profiles were analyzed.ResultsEight Chinese patients exhibited elevated plasma total homocysteine (tHcy) levels (85.7–227.2 μmol/L). These patients revealed 11 variants across 3 genes, including 2 novel variants and 9 previously reported pathogenic variants. All patients were compound heterozygotes. Six patients (P1–6) were diagnosed with cystathionine β-synthase (CBS) deficiency, with seven CBS variants identified. Among these, one novel frameshift variant (c.860del) was detected. Major clinical manifestations included marfanoid features, lens dislocation, myopia, mild developmental delay, osteoporosis, epilepsy, and cerebral venous sinus thrombosis, with ectopia lentis or myopia as common early signs (ages 4–6 years). One child had methylenetetrahydrofolate reductase deficiency, with two variants (c.1632+2T>G, c.1552C>T) and the variant c.1552C>T was novel. The patient displayed developmental delays, microcephaly, and status epilepticus. One child (P8) showed elevated tHHcy and urine methylmalonic acid levels, attributed to cobalamin C deficiency caused by MMACHC variants (c.482G>A, c.609G>A). He presented with epilepsy, weakness in both lower limbs, cognitive dysfunction, and urinary incontinence. Comprehensive interventions including dietary and pharmacological therapies, significantly reduced tHHcy levels in most cases.DiscussionElevated tHcy is an important biomarker for inherited HHcy. Genetic testing is crucial for precise diagnosis, therapy initiation, and genetic counseling. Two novel pathogenic variants were identified, enriching the variant spectrum for inherited HHcy.